Numerical analysis on a constant rate of kinetic energy change based a two-stage ejector-diffuser system - Sethi, Virendra Kumar (Strojniški vestnik, 2022)
Supersonic ejector energy flow devices are extensively used in various applications, such as pumping, mixing, compression, etc. The conventional single-stage ejector (SSE) design approaches are inefficient for modelling an efficient ejector because of their inefficiency in minimizing mixing losses in the mixing chamber, thermodynamic shock in constant area diffuser, and utilization of redundant discharged momentum at the exit of the first stage. The physics-based single-stage ejector design has better solutions because it minimizes irreversibility due to thermodynamic shocks. The present study utilizes the constant rate of a kinetic energy change physics-based approach to design a two-stage ejector (TSE) for water vapour. The computational fluid dynamics (CFD) tool ANSYS-Fluent has been utilized to predict flow characteristics. The performance of the ejector-diffuser system has also been compared with a single-stage ejector. It is found that the performance of TSE is 70 % higher than that of the performance of SSE.
Keywords: CFD; CRKEC; CRM; curkovne črpalke; dvostopenjski ejektorji; ejectors; ejektorji; enostopenjski ejektorji; single-stage ejectors; two-stage ejectors